How are elite tennis matches won at Wimbledon? A comparison of close and one-sided contests - Fitzpatrick, A.; Stone, J. A.; Choppin, S.; Kelley, J. (European Journal of Sport Science, 2024)
Notational analysis investigations of several sports have suggested that the performance characteristics associated with success differ by match closeness. It is not known whether this is the case in tennis. Therefore, this study aimed to first develop operational definitions for closely contested and one-sided tennis matches, then establish whether the important performance characteristics in elite grass court tennis differ by match closeness. Data from 365 men and 374 women's Wimbledon single matches played between 2015 and 2017 were analyzed. Irrespective of match closeness, points won of 0-4 shot rally length, first serve points won and baseline points won were associated with winning matches, and forced errors and unforced errors were associated with losing matches, for both sexes. Spearman's rank-order correlations demonstrated excellent agreement between the importance of the performance characteristics in closely contested and one-sided men (rs = 0.89, p < 0.001) and women's matches (rs = 0.90, p < 0.001), respectively. Findings suggest that expected match closeness (of an upcoming match) should not necessarily influence decision-making around practice design and match-play strategy. Additionally, the operational definitions developed for closely contested and one-sided matches developed here could be used in future studies to investigate different competitive contexts.